Total reflection X-ray fluorescence for determination of radium in water simulated by MCNP6.2 code. (September 2021) - Hermógenes, G.; Oliveira, E.B.; Zambianchi, J.K.; Zambianchi, P.
Abstract: The measurement of trace concentrations of radium in water by total reflection X-ray fluorescence (TXRF) is addressed. X-ray fluorescence spectra and the calibration plot data were numerically simulated by the MCNP6.2 code using a 2482 Bq / g 226 Ra standard solution, with gallium added as an internal standard element. From the simulations, the lower limit of activity concentration measurable by this technique is 0.047 Bq / L . The results also show that the detection limit 2.56 × 10 −11   g can be achieved in a molybdenum X-ray tube in TXRF geometry, provided the samples are previously evaporated to a dry residue. For drinking water, it requires a complete evaporation of 937 mL containing 1.0 Bq / L of 226 Ra, which is the current upper limit of activity concentration recommended by the World Health Organization (WHO) guideline. Highlights: Determination of radium concentration in water by total reflection X-ray fluorescence is proposed, based on numerical simulations of the MCNP6.2 code. The simulations use parameters of a molybdenum X-ray tube set in the total reflection geometry. Limit of detection given by TXRF technique allows measuring trace amounts of  226 Ra in drinking water.